Development and Characterization of Innovative Nutraceutical Corn Jam - Ahsan, Mehak; Asif, Rida; Wasi, Nitasha; Tariq, Sana; Fawad, Summaiyah; Ejaz, Tanzila; Raza, Rashid (Journal of Research (Science), 2025)
Many fruit jams are available in the market such as strawberry, pineapple, apricot, and orange but no jam has been reported to be formulated with corn. This prompted the idea of establishing corn based jam. This study was therefore, aimed to produce a new innovative corn jam. Standard methods were applied for sensory analysis and physicochemical (proximate) analysis. Among the various combinations, the newly developed corn jam containing 155g corn and 93g jaggery was found to be better for its nutritional quality and sensory evaluation. All three samples of newly prepared corn jam have been found highly acceptable according to sensory evaluation. The pH, acidity, brix, moisture, ash, protein, fat, fiber, carbohydrates and antioxidant activity of sample selected on the bases of organoleptic properties were found to be 3.5, 0.1%, 68.5 o, 1.74%, 2.22%, 0.21%, 2.0%, 0.01%, 65.99% and 7.89% respectively. On the sensory point of view, all three samples of the presently developed corn based jam were found highly acceptable. Viscosity and consistency analysis showed good quality attributes of corn based jam. The newly developed corn based jam also has the market competent price therefore the product is likely to gain the attraction of consumer and improves the market trends.